2021
DOI: 10.2147/opth.s339393
|View full text |Cite
|
Sign up to set email alerts
|

Brolucizumab: Evaluation of Compassionate Use of a Complex Anti-VEGF Therapy

Abstract: Objective: To report a consecutive series of compassionate, off-label use of intravitreal brolucizumab as a rescue therapy for complex, non-responsive macular edema. This report delineates primary diagnosis, indications for treatment, adverse events, and visual and anatomic outcomes after intravitreal brolucizumab. Methods: A retrospective review of a consecutive clinical case series of 110 eyes treated with intravitreal brolucizumab between January 1st and March 1st. 2020. All patients were included if they r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This benefit was also maintained at weeks 44 and 48. These results corroborate previous studies [ 15 , 17 , 19 , 20 ]. The SHRM resolution was comparable for both brolucizumab and aflibercept treated eyes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This benefit was also maintained at weeks 44 and 48. These results corroborate previous studies [ 15 , 17 , 19 , 20 ]. The SHRM resolution was comparable for both brolucizumab and aflibercept treated eyes.…”
Section: Discussionsupporting
confidence: 93%
“…The HAWK and HARRIER phase 3 trials have shown the non-inferiority of brolucizumab against aflibercept, with more than 50% of patients with nAMD maintaining the BCVA gains on q12w dosing interval throughout the study period of 48-96 weeks [14,15]. In addition, brolucizumab has shown effectiveness in improving visual acuity in several studies [13][14][15][16][17][18][19][20]. However, the treatment for nAMD may respond differently in patients at different stages of the disease [21] as well as the treatment may differ in patients with diverse ethnicity and genetic make-up [4,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Brolucizumab has proved to be capable of controlling retinal fluid in MNV in several reports [15,16,[33][34][35]. In the Hawk and Harrier registrative trials, the proportions of eyes with IRF and/or SRF at week 96 were lower in the brolucizumab arm compared to the aflibercept arm [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…77 Murray et al studied the off-label use of intravitreal brolucizumab as a rescue therapy in a series of eyes with vision compromising macular oedema (MO) secondary to different ocular conditions, which had not responded to prior repetitive anti-VEGF or steroid treatment. 78 Analysis showed significant reduction of MO as well as marked BCVA improvement for all study participants following brolucizumab administration. 78 A summary of the real-world studies is depicted in Table 2.…”
Section: Retinal Vein Occlusion (Rvo) and Other Ocular Disordersmentioning
confidence: 84%
“…78 Analysis showed significant reduction of MO as well as marked BCVA improvement for all study participants following brolucizumab administration. 78 A summary of the real-world studies is depicted in Table 2.…”
Section: Retinal Vein Occlusion (Rvo) and Other Ocular Disordersmentioning
confidence: 84%